NEWER METHODS OF EXTRACTION OF TEETH - DR. M.P.SANTHOSH KUMAR, (International Journal of Pharma and Bio Sciences, 2015)
Atraumatic extraction methods are deemed to be important to minimize alveolar bone loss after tooth extraction and to facilitate subsequent implant restoration and optimal esthetic outcomes. With the advent of such techniques, exodontia is no more a dreaded procedure in anxious patients. Newer systems and techniques for extraction of teeth have evolved in the recent few decades.This article reviews and discusses new techniques to make simple and complex exodontias more predictable and efficient with improved patient outcomes. This includes physics forceps, powered periotome, piezosurgery, benex extractor, Sonic instruments for bone surgery, lasers.